'Just doing their job?' Journalism, online critique and the political resignation of Metiria Turei. (July 2021) - Phelan, Sean; Salter, Leon A
When Metiria Turei resigned as co-leader of the Green party of Aotearoa New Zealand in August 2017, there was clear disagreement about the role played by journalism in her resignation. The controversy began after Turei confessed to not disclosing full information to the authorities about her personal situation as a welfare recipient in the 1990s. Journalists insisted they were simply 'doing their job' by interrogating Turei's story, while online supporters accused the media of hounding her. This article examines the media politics of the controversy by putting Carlson's concept of metajournalistic discourse into theoretical conversation with Laclau and Mouffe's discourse theory, especially their concept of antagonism. We explore what the case says about traditional journalistic authority in a media system where journalism is increasingly vulnerable to online critique from non-journalists.